MENGGAGAS NASKH TAWFĪQĪ: Kritik dan Rekonsiliasi atas Teori-Teori Naskh - Aldi Hidayat; Abd. Mun’em (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2023)
Abstract Naskh is the most productive topic that creates differences, both between classical scholars and contemporary scholars, as well as between classical scholars themselves. In general, the themes of the naskh produce four theories: naskh as the erasure of verses from the Qur'an, wether legal or redaction or both at once, naskh as the erasure of the previous prophet's Shari'ah; naskh as the erasure of miracles and naskh as the postponement of the application of verses of the Qur'an. So far, these four theories have not been reconciled, even though in fact there is no contradiction between all of these theories. Therefore, by adopting Aksin Wijaya's appreciative-critical and critical-appreciative thinking framework, the author will position each naskh theory as a friend in speaking as well as an opponent in exchanging ideas or vice versa. Firstly, where is the gap between each theory, so that it allows the author to criticize and at the same time stop its constancy not only as a theory, but also to stop its constant contradiction with other theories? Second, how to formulate each theory into a new theoretical building which the author calls naskh tawfīqī (reconciliatory naskh)? These two formulations of the problem result in the conclusion that: first, there is no contradiction between mask theories, so it is not appropriate to side with one while ignoring the other. Second, naskh tawfīqī as a novelty of this article is a new reading of verses that are considered contradictory by emphasizing the context of the verses, both internal and external and then looking for contextual equivalents in the contemporary world of thought. Keywords: naskh, tawfīqī, critic, reconciliation